Mexican experience in the implementation of the RothC-26.3 model of the dynamics of organic carbon in soils: scope and limitations (TERRA LATINOAMERICANA, 2022)
The use of models of the dynamics of organic carbon in soils has been emphasized for the implementation of different public programs, including greenhouse gas inventories. The RothC 26.3 model (RothC) is one of the most used worldwide in the study of C dynamics. The objective of this study was to make a synthesis of the performance of the RothC model in predicting changes in SOC in plots, sites, systems and regions. As well as application in scenarios of land use change (LUC) and cropping systems using short-term (
Keywords: initialization; soil organic matter; crop systems; secondary vegetation